Ecological divergence and hybridization of Neotropical Leishmania parasites - Frederik Van den Broeck; Nicholas J. Savill; Hideo Imamura; Mandy Sanders; Ilse Maes; Sinclair Cooper; David Mateus; Marlene Jara; Vanessa Adaui; Jorge Arévalo; Alejandro Llanos‐Cuentas; Lineth García; et al. (My University, 2020)
Significance Parasites are interesting models for studying speciation processes because they have a high potential for specialization, thanks to the intimate ecological association with their hosts and vectors. Yet little is known about the circumstances under which new parasite lineages emerge. Here we studied the genome diversity of parasites of the Leishmania braziliensis species complex that inhabit both Amazonian and Andean biotas in Peru. We identify three major parasite lineages that occupy particular ecological niches and show that these emerged during forestation changes over the past 150,000 y. We furthermore discovered that meiotic recombination between Amazonian and Andean lineages resulted in full-genome hybrids presenting mixed mitochondrial genomes, providing insights into the genetic consequences of hybridization in parasitic protozoa.
Keywords: Biology; Evolutionary biology; Genome; Leishmania braziliensis; Mitochondrial DNA; Population; Phylogenomics; Nuclear gene; Phylogenetics; Genetics; Clade; Leishmaniasis; Gene; Cutaneous leishmaniasis; Sociology; Demography; Biology; Evolutionary biology; Genome; Leishmania braziliensis; Mitochondrial DNA; Population; Phylogenomics; Nuclear gene; Phylogenetics; Genetics; Clade; Leishmaniasis; Gene; Cutaneous leishmaniasis; Host-Parasite Interactions genetics; Host-Parasite Interactions genetics; Host-Parasite Interactions genetics; Host-Parasite Interactions genetics; Humans; Humans; Humans; Humans; Leishmania braziliensis genetics; Leishmania braziliensis genetics; Leishmania braziliensis genetics; Leishmania braziliensis genetics; Leishmania braziliensis pathogenicity; Leishmania braziliensis pathogenicity; Leishmania braziliensis pathogenicity; Leishmania braziliensis pathogenicity; Peru epidemiology; Peru epidemiology; Peru epidemiology; Peru epidemiology; Leishmaniasis, Cutaneous genetics; Leishmaniasis, Cutaneous genetics; Leishmaniasis, Cutaneous genetics; Leishmaniasis, Cutaneous genetics; Leishmaniasis, Cutaneous epidemiology; Leishmaniasis, Cutaneous epidemiology; Leishmaniasis, Cutaneous epidemiology; Leishmaniasis, Cutaneous epidemiology; Leishmaniasis, Cutaneous parasitology; Leishmaniasis, Cutaneous parasitology; Leishmaniasis, Cutaneous parasitology; Leishmaniasis, Cutaneous parasitology; Ecosystem; Ecosystem; Ecosystem; Ecosystem; Genetic Speciation; Genetic Speciation; Genetic Speciation; Genetic Speciation; Genome, Mitochondrial genetics; Genome, Mitochondrial genetics; Genome, Mitochondrial genetics; Genome, Mitochondrial genetics; Phylogeography; Phylogeography; Phylogeography; Phylogeography; Forests; Forests; Forests; Forests; Health Sciences Medicine Public Health, Environmental and Occupational Health Research on Leishmaniasis Studies; Physical Sciences Environmental Science Ecology Parasite Biology and Host Interactions; Life Sciences Immunology and Microbiology Parasitology Parasites and Host Interactions